Cyp3a4 *1b gene polymorphism in coronary artery disease patients with obesity undergoing statin treatment - KARAALP, ATİLA; SÜNBÜL, MURAT (Bentham Science Publishers, 2021)
Objective: Coronary artery disease (CAD) is one of the leading causes of morbidity and mortality worldwide and statins are frequently prescribed in the treatment of CAD to help lower blood cholesterol levels. Since the main enzyme involved in the metabolism of statins is CYP3A4, we aimed to investigate the effect of CYP3A4 * 1B genotypes on plasma lipid profile in Turkish cardiovascular disease subjects with and without obesity taking statin. Materials and Methods: The study group consisted of 85 cardiovascular disease patients who were prescribed statins and had routine biochemical analysis data. Polymerase chain reaction followed by restriction fragment length polymorphism (PCR-RFLP) assay was performed for genotyping of CYP3A4 *1B (rs2740574) polymorphism. Results: Genotype distribution of CYP3A4 *1B polymorphism was found for homozygous wild (AA) and homozygous polymorphic (GG) genotypes as 94.1% and 5.9%, respectively. We did not detect patients with heterozygous genotype in our study group. We found that the mean LDL-c, TG and TC levels were higher in patients with CYP3A4 *1B GG compared to the AA genotype. The frequency of CYP3A4 *1B GG genotype frequency (9.5%) was detected higher in the obese patients compared to the non-obese patients (7.7%) (χ2=0.037, p=0.85). Conclusion: Our results demonstrate that CYP3A4 *1B homozygous polymorphic genotype distribution tends to be higher in obese patients compared to non-obese patients with cardiovascular disease which may point to *1B allele having a slight effect on serum lipids during statin therapy. Ad-ditional studies with higher samples are needed for evaluating the role of CYP3A4 *1B on lipids in patients under statin therapy. © 2021 Bentham Science Publishers.
Keywords: 290 A>G; Cardiovascular disease; CYP3A4; Obesity; Serum lipids; Statins